2019
DOI: 10.1111/jdi.13070
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in non‐obese patients with type 2 diabetes is associated with low muscle mass: The Multicenter Study for Clarifying Evidence for Sarcopenia in Patients with Diabetes Mellitus

Abstract: Aims/Introduction Hyperglycemia is a risk factor for sarcopenia when comparing individuals with and without diabetes. However, no studies have investigated whether the findings could be extrapolated to patients with diabetes with relatively higher glycemic levels. Here, we aimed to clarify whether glycemic control was associated with sarcopenia in patients with type 2 diabetes. Materials and Methods Study participants consisted of patients with type 2 diabetes (n = 746, the average age was 69.9 years) and an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 37 publications
5
95
2
4
Order By: Relevance
“…Reduced muscle fiber number and/or size is associated with a decrease in muscle function and can be caused by age [44], disuse [45] and illness [46]. Strong evidence suggests that diabetes is associated with muscular changes such as reduced muscle strength [47], power [48], mass [49], quality [48], and endurance and fiber type switch [6,50] termed as diabetic myopathy [6,51]. Our findings show that in the hyperglycemic environment, skeletal muscle in both rats and women decrease the number and area of fast fibers and an increase in the number of slow fibers.…”
Section: Plos Onementioning
confidence: 99%
“…Reduced muscle fiber number and/or size is associated with a decrease in muscle function and can be caused by age [44], disuse [45] and illness [46]. Strong evidence suggests that diabetes is associated with muscular changes such as reduced muscle strength [47], power [48], mass [49], quality [48], and endurance and fiber type switch [6,50] termed as diabetic myopathy [6,51]. Our findings show that in the hyperglycemic environment, skeletal muscle in both rats and women decrease the number and area of fast fibers and an increase in the number of slow fibers.…”
Section: Plos Onementioning
confidence: 99%
“…In women, this effect was not seen leading to the potential sex differences in protein metabolism under diabetic conditions. T2DM is associated with lower skeletal muscle mass [84,85] and decreased muscle mass is correlated with poorer glycemic control [86]. Given these findings of decreased muscle mass with variable amino acid flux in T2DM, it remains difficult to quantify how much amino acids supply gluconeogenic carbons under diabetic conditions.…”
Section: Changes To Gluconeogenic Precursor Levels In T2dmmentioning
confidence: 99%
“…3 We previously reported a linear positive association between glycated hemoglobin (HbA 1c ) levels and frequency of sarcopenia in middle-aged to older patients with type 2 diabetes (age range: 38-96 years). 4 Another study in older patients with diabetes also reported HbA 1c !8.0% (64 mmol/mol) as a risk factor for the decline in muscle quality, independent of the duration of diabetes. 5 Additionally, a few studies found that blood glucoseelowering therapy with insulin sensitizers could prevent loss of muscle mass.…”
mentioning
confidence: 96%